An educational intervention to promote a culture of gender equity among persons with traumatic brain injury and caregivers: A pilot study - Hanafy, Sara; Quilico, Enrico; Haag, Halina (Lin); Khoo, Yuelee (Ben); Munce, Sarah; Lindsay, Sally; Colantonio, Angela; Mollayeva, Tatyana (Frontiers in Rehabilitation Sciences, 2023)
Background: Traumatic brain injury (TBI) outcomes are dependent on patients’ biological sex (e.g., hormone levels) and sociocultural gender (e.g., norms, responsibilities). Informal caregivers additionally experience disruptions to identity and roles post-TBI. However, information on this topic remains largely unavailable to patients and caregivers. Purpose: This study aimed to determine the effectiveness of a one-time educational intervention on sex and gender influences in TBI for patients and informal caregivers. Materials and Methods: We conducted a pilot pre-test/post-test randomized control-group design study. Groups (i.e., passive, active and control) consisted a total of 16 persons with TBI and caregivers (75% persons with TBI, 63% women). Individual and group learning gains, and group-average normalized gain, were computed for three learning domains: knowledge, attitude, and skill. An intervention with an average normalized gain of ≥ 30% was considered effective. Educational intervention evaluation and qualitative comments post-participation were summarized. Results: The passive group demonstrated the highest average normalized gain across the three learning domains, including 100% for knowledge, 40% and 61% for attitude, and 37% for skill. The remaining groups did not reach an average normalized gain of ≥ 30%, except for the attitude domain of the control group (33% and 32%). Two key categories were identified qualitatively: (1) gendered self-expectations post-injury and (2) implications of gender stereotypes in rehabilitation, including the need for rehabilitation treatment to look beyond sex and gender. The post-participation educational session evaluation conveyed high appraisal of content, organization, and usability of the intervention. Conclusion: A one-time passive educational intervention on sex and gender in TBI may improve knowledge, attitude, and skill on the topic of sex and gender among adults with TBI and caregivers. Obtaining knowledge and skill on sex and gender effects in TBI can potentially help persons with TBI and caregivers adapt to changes in roles and behaviours post-injury.